Analyzing the Correlation Between Vocabulary Mastery and Translation Performance Among Students - roswati, roswati; nurdiana, nurdiana; afrizal, afrizal; sofia, nur zarit (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Translating words from the source language to the target language would be challenging for students with a large vocabulary. Translation facilitates language learning. As a result, students lacking a vast vocabulary will be unable to translate the meaning of a language. The goal of this study was to determine whether students' vocabulary competency and translation ability are connected. Correlation research was used in the design, and quantitative research was performed in this study. Simple random sampling was employed to choose the sample. Out of 140 populations, 29 students made up the research sample. The researcher employed multiple-choice tests with 20 items and a translation test with a single text to gather data for the study. In this study, the Pearson Product Moment formula was calculated using SPSS. Following the hypothetical exam, the results showed that students' translation skills and vocabulary mastery were positively correlated. According to the data analysis that SPSS calculated, α=0.05 and Sig (P Value) = 0.000 were found. Given that Sig (P Value) = 0.000 < α=0.05, it indicates that Ha was accepted while Ho was rejected. Additionally, the outcome indicates that the r-observed was 0.611. At 1% significance level, the r-table score was 0.470, meaning that r-observed > r-table (0.611 > 0.470); at a 5% significance level, the r-table score was 0.367, meaning that r-observed > r-table (0.611 > 0.367). In conclusion, there is a relationship between students' capacity to translate and their command of language.